Convergence of difference additive functionals under local conditions on their characteristics - Kartashov, Yu. N.; Kulik, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
For additive functionals defined on a sequence of Markov chains that approximate a Markov process, we establish the convergence of functionals under the condition of local convergence of their characteristics (mathematical expectations).